Introducing patient and public involvement practices to healthcare research in Austria: strategies to promote change at multiple levels - Stefan Tino Kulnik; Raphaela E Kaisler; Elisabeth Klager; Maria Kletecka-Pulker; Eva Schaden; Andreas Stainer-Hochgatterer (BMJ Open)
Background Patient and public involvement (PPI) in research is well-established in the UK. However, it can be challenging to introduce PPI to research communities where there is limited prior knowledge, experience or appreciation of PPI. We aimed to explore current PPI practices, experiences and ethical and operational challenges with PPI within our own research community in Austria, to inform strategies for supporting PPI in Austria going forward.Methods We surveyed scientists at 21 research institutes of the Ludwig Boltzmann Gesellschaft (LBG) and representatives of 32 medical and university research ethics committees in Austria using online questionnaires. We analysed quantitative data using descriptive statistics, and we collated textual responses to open questions. We combined survey data with anecdotal evidence from our personal experience to summarise current challenges around implementing PPI in Austria.Results Nineteen scientists from nine research institutes indicated generally positive attitudes towards PPI. However, the majority reported they rarely or never involved patients and members of the public in roles of consultation, collaboration or control in research. Six of eight ethics committees were unfamiliar with PPI. We discern five current challenges to implementing PPI in Austria: lack of knowledge and skills for PPI among scientists, scepticism about the usefulness of PPI, conflation of PPI with qualitative research, uncertainty about ethical requirements for PPI and uncertainty about publishing PPI activities.Discussion We suggest that the provision of guidance about ethical requirements of PPI is a strategic priority. To address this, and following on from a recently introduced PPI training and grant scheme by the LBG, our surveys have initiated a dialogue with ethics committees and have informed the development of a checklist for ethical aspects of PPI.Conclusion Our experiences may provide useful examples to others who seek to introduce or strengthen PPI practices within their own research communities.